Pharmacological prolyl hydroxylase inhibition enhances high‐intensity exercise capacity in mice - Koji Takemura; Motoki Odawara; Hiroshi Nishi; Takaaki Higashihara; Yoko Yoshida; Koichi Nakazato; Nobuharu L. Fujii; Naokata Ishii; Reiko Inagi; Tetsuhiro Tanaka; Masaomi Nangaku (Physiological Reports)
Abstract Increased blood hemoglobin concentration theoretically promotes oxygen delivery to the periphery. Clinically, in addition to recombinant human erythropoietin analogs, prolyl hydroxylase (PH) inhibitors to stabilize the expression of hypoxia‐inducible factor (HIF) protein were recently approved for the treatment of anemia in chronic kidney disease. However, whether the new agent helps enhance physical exercise capacity remains a matter of controversy. Treatment of C57BL/6J mice via oral gavage with roxadustat of 30 mg/kg three times per week for 5 weeks elevated the blood hemoglobin concentration, upregulated the HIF‐downstream gene expression of the muscle, and enhanced a high‐intensity exercise performance measured with a treadmill running exhaustion test, compared to those treated with vehicle, while total body weight or skeletal muscle mass was comparable. This physical effect depended on the increase in blood hemoglobin concentration, as confirmed by mice hemodiluted to control hemoglobin concentrations through phlebotomy followed by infusion of the approximate volume of phosphate‐buffered saline. In conclusion, oral administration of the HIF‐PH inhibitor to mice increased high‐intensity exercise capacity as well as elevated blood hemoglobin concentration. The finding implies the versatile effects on humans taking HIF‐PH inhibitors, as well as the risk of them being abused for blood doping.